Symptom management and palliative care in advanced basal cell carcinoma - Pietrzyński, Łukasz; Kaspera, Maciej; Symela, Joanna; Rajchel, Mateusz; Pietrzyńska, Tatiana (Medycyna Paliatywna/Palliative Medicine, 2018)
Basal cell carcinoma (BCC) is the most frequent malignant neoplasm of the skin. If a neoplasm is recognized and an accurate treatment is implemented, the prognosis is very positive. However, negligence of the neoplasm could lead to infiltration of the adjacent bone, cartilaginous or vascular structures as well as the eyeball, which could result in its damage and anatomical deformations. The presented case illustrates the possible aggressive and destructive impact of facial skin basal cell carcinoma with rare involvement and destruction of the underlying bone. Long-term growth of the neoplasm resulted in an ulcerative lesion of the forehead area, disability, severe depression and social isolation, as well as numerous somatic complications. This article presents the issues and challenges of palliative care of a patient with advanced facial skin cancer.